The water resource: ethical? - Barba Nureña, José S. (2019)
The current and projected impact of the use of water resources is based on data from numerous researches committed to the sustainability of the environment and focuses on the current crisis that is experienced by the good management of the hydric resource that the planet has and that is of vital importance for the life and development of the human species. seen and analyzed from the ethical point of view and how this resource is handled, vital for the survival not only of the human species.As the years go by, it will become more scarce, affecting primarily human development and the survival of the planet. These new forms will generate economic trends but an ethical background is very well used that will never be bad. If there lies a more systemic approach, we must not stop acting well, withouthaving to resort to alternatives that give us anxieties that are conditions for opportunists.Today, even with the mediation of international agreements, it has become increasingly difficult to comply with the goals formulated to return to such conditions that allow the survival of man and satisfy with it the principle of responsibility formulated by Hans Jonás: “Obra de tal modo que los efectos de tú acción sean compatibles con la permanencia de una vida humanaauténtica en la tierra” (Rama, 2009).